Fertilización foliar con humus líquido de lombriz en dos poaceas (Panicum máximum y Brachiaria brizantha) y su efecto en las características agronómicas y rendimiento de forraje en Zungarococha, Perú - 2020 - Angulo Davila, Henry (2022)
The National University of the Peruvian Amazon in the Faculty of Agronomy, took the research work entitled "FOLIAR FERTILIZATION WITH LIQUID WORM HUMUS IN TWO POACEAS (Panicum maximum and Brachiaria brizantha) AND ITS EFFECT ON THE AGRONOMIC CHARACTERISTICS AND YIELD OF FORAGE IN ZUNGAROCOCHA, PERU – 2020”. In an experimental area of 195.5 m2. With a Complete Randomized Block Design (DBCA), with a factorial arrangement of 2 x 2, with four treatments and six repetitions, the evaluations were carried out at the tenth week after sowing with plots of 3 mx 1.2 m (3.6 m2) and the treatments that were put into study were T1 (F1PB1), T2 (F1PP2), T3 (F2PB1) and T4 (F2PP2), where F = Fertilization, and F1 = 25% liquid worm humus + 75% water, F2= 50% Liquid Earthworm Humus + 50% water, and P = Pasture, where PB = Pasture Brachiaria brizantha cv. Marandu, and PP = Panicum maximum grass cv. Tanzania, obtaining the following results: With the F2PPm treatment (50% liquid worm humus + 50% water) in the two poaceae, Panicum maximum and Brachiaria brizantha and Bachearia brizantha cv. Marandu, the best results were achieved in aerial biomass (green matter) with 2.03 and 1.84 kg/m2 respectively. With the F2PPm and F2PBb treatments, achieving a green matter production of 20266.67 kg/ha and 18383.33 kg/ha per cut